1996
DOI: 10.1007/bf00834525
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m tetrofosmin rest/stress myocardial SPET with a same-day 2-hour protocol: comparison with coronary angiography A Spanish-Portuguese multicentre clinical trial

Abstract: Technetium-99m tetrofosmin (Myoview) has unique properties for myocardial perfusion imaging very early after injection of the tracer. We used a very short same-day rest/stress protocol, to be performed within 2 h and evaluated its diagnostic accuracy. The study included 144 patients from seven Spanish and four Portuguese centres with a diagnosis of uncomplicated coronary artery disease (CAD); 78 patients (54%) had no history of prior myocardial infarction. Patients were injected with Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…This means that there is a trade-off between the image quality in terms of a high signal-to-noise ratio in the first study and the unwanted contribution from the residual activity from this study in the second study. Clinical studies support the usefulness of both 1-and 2-day protocols (Berman et al, 1994;Bratt et al, 1994;Van Train et al, 1994;Montz et al, 1996), but a detailed comparison of these protocols has, to our knowledge, not been performed previously.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…This means that there is a trade-off between the image quality in terms of a high signal-to-noise ratio in the first study and the unwanted contribution from the residual activity from this study in the second study. Clinical studies support the usefulness of both 1-and 2-day protocols (Berman et al, 1994;Bratt et al, 1994;Van Train et al, 1994;Montz et al, 1996), but a detailed comparison of these protocols has, to our knowledge, not been performed previously.…”
Section: Introductionmentioning
confidence: 90%
“…, 1994; Van Train et al. , 1994; Montz et al. , 1996), but a detailed comparison of these protocols has, to our knowledge, not been performed previously.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…27 Clinical studies have shown that tetrofosmin SPECT gives an extremely accurate diagnosis of CAD. [28][29][30][31][32] A BMIPP SPECT study cannot be performed at the time of admission and the following day is the earliest. Accordingly, the appearance of abnormal BMIPP findings may be quite limited.…”
Section: Methodological Considerationmentioning
confidence: 99%
“…MIBI çalışmasında olduğu gibi, stres ve istirahat esnasında olmak üzere iki ayrı enjeksiyon yapılması gerekir. MIBI'ye göre daha erken görüntüleme avantajına sahiptir (4,8).…”
Section: Miyokard Perfüzyon Sintigrafisinde Kullanılan Radyofarmasötiunclassified